Paul and imperial divine honors: Christ, Caesar, and the Gospel - Burnett, Clint (Wm. B. Eerdmans Publishing Co., 2024)
Intro -- Title Page -- Copyright -- Dedication -- Contents -- List of Figures -- List of Tables -- Foreword by Pheme Perkins -- Preface -- Acknowledgments -- List of Abbreviations -- List of Epigraphic Conventions -- Introduction -- 1. Imperial Divine Honors -- 2. Imperial Divine Honors, Paul, and the Philippian Church -- 3. Imperial Divine Honors, Paul, and the Thessalonian Church -- 4. Imperial Divine Honors, Paul, and the Corinthian Church -- Conclusion -- Appendix 1: Inscriptions -- Appendix 2: Reconstructed Julio-Claudian Imperial Calendar in Philippi and Corinth -- Bibliography.